Pengaruh Financing to Deposit Ratio, Biaya Operasional dan Pendapatan Operasional terhadap Return on Assets pada Bank Umum Syariah di Indonesia Periode 2020-2024. - Nur Alya Nanda; Chalid Imran Musa; Annisa Paramaswary Aslam; Anwar Anwar; Abdul Rahman (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
This study aims to analyze the effect of the Financing to Deposit Ratio (FDR) and Operating Expenses to Operating Income (BOPO) on Return on Assets (ROA) in Islamic Commercial Banks in Indonesia. This research employs a quantitative approach using secondary data in the form of annual financial statements of Islamic Commercial Banks registered with the Financial Services Authority (OJK) during the period 2020–2024. The sample consists of 12 Islamic Commercial Banks selected using purposive sampling based on data availability and completeness. Data were analyzed using panel data regression with the assistance of Eviews 13. Model selection was conducted through the Chow test, Hausman test, and Lagrange Multiplier test. The results show that the Financing to Deposit Ratio (FDR) has a significant effect on Return on Assets (ROA), indicating that banks’ ability to manage financing distribution plays an important role in determining asset performance. In addition, Operating Expenses to Operating Income (BOPO) is also proven to have a significant effect on Return on Assets (ROA), suggesting that the management of operational activities contributes substantially to banks’ financial performance. Overall, these findings support agency theory, which states that managerial performance as an agent in managing funds and operational activities has a direct impact on the achievement of banks’ financial performance.